Induction of mutation and measurement of genetic variability in sugarcane genotypes (Revista de Ciências Agroveterinárias, 2017)
The widespread usage of commercial varieties of sugar that are adapted to the agricultural system and come from parents with a small genetic distance can lead to a narrowing of the genetic basis of sugarcane. This study aimed to induce mutations and evaluate the genetic distance among the sugarcane mutants produced by different multivariate techniques. Mutations were induced and then the genetic distance among these sugarcane mutants was evaluated with the use of multivariate techniques. The study was conducted in the experimental area of the UFSM, Frederico Westphalen, RS. The genotype used for mutation induction was IAC 873396. The induction process proceeded with the placement of buds in a solution of the mutagenic agent MMS (Methyl Methane Sulfonate). A total of 22 mutations and six commercial checks were evaluated for 12 traits of agronomic interest. The analyses were: the evaluation of individual averages, Tocher’s grouping, average Euclidean distance, an analysis of principal components, and the relative contribution of characteristics. The mutation induction process generated significant patterns of genetic variability among sugarcane mutants verified by three multivariate analyses. The UPGMA clustering methods, Tocher and principal component analysis revealed similar results related to the dissimilarity of sugarcane genotypes. Genotypes 20, 24, and 10 were greater than the general average of genotypes and have a high genetic dissimilarity for traits. The yield of stems, bagasse mass, and the yield sugarcane broth are sufficient to characterize a set of sugarcane genotypes.
Keywords: agronomic performance; genetic variability; Saccharum officinarum L.